IDENTIFICATION DE RÉGIONS HOMOGÈNES DU POINT DE VUE HYDROLOGIQUE. ÉTUDE DE CAS: LA RÉGION DE LA COURBURE DE L’ARC CARPATIQUE - LILIANA ZAHARIA (Revue Roumaine de Géographie)
Identification of homogeneous hydrological regions. Case study: the Carpathian Curvature region. The identification of homogeneous regions of the hydrological point of view constitutes a preliminary stage for certain methods of hydrological regionalization used in the practice (for example the method of the “index flood”) to estimate a hydrological variable of interest. The precision of the estimations realized by these methods is influenced by the degree of homogeneity of the considered region. The aim of this paper is to try identifying homogeneous hydrological regions in the space of the external Carpathian Curvature region, for refining the estimations of the annual maximum flows of different return periods obtained by the “index flood” regionalization method. As statistical test we used the test of the measure of the heterogeneousness, proposed by Hosking and Wallis (1993, 1997). The conclusions are the following ones: i) the ensemble of the study area is heterogeneous from the point of view of the conditions of formation of the maximum flows; ii) inside this area on we can separate two sub-regions – hilly and mountainous –which heterogeneity is much more reduced, the hilly region being able to even be considered as homogeneous.